Photometry of Betelgeuse from the National Observatory, Nagarkot, Nepal - Koju, RK; Aryal, B; Shahi, SR (Scientific World, 2012)
Analyzing the visual flux collected by 16 inch Meade LX200GPS telescope placed at National Observatory, Nagarkot, Nepal in FITS format, we noticed a significant asymmetrical feature along the southern region of red giant Betelgeuse. The symmetrical feature is deviated widely when moving from inner to outer layer particularly in the southern direction. The southern region is expanded outward while the northern region is compressed. The region lying in the other two direction remains in intermediate. Scientific World, Vol. 10, No. 10, July 2012 p7-12 DOI: http://dx.doi.org/10.3126/sw.v10i10.6853